Study Of Cold Chain Practices at Community Health Centers of Damoh District Of Madhya Pradesh - Amarnath Gupta; Rekha Gupta (Medsci Publications, 2015)
Introduction: Vaccination is one of the most effective disease preven- tion strategies and potency of vaccine is dependent on effective man- agement of cold chain at all levels of vaccine handling. An effective cold chain maintenance system is the backbone of success of any im- munization program. The study was done to assess the status of cold chain and vaccine storage practices in Damoh district of Madhya Pradesh. Methodology: Cross-Sectional Study was done using a structured questionnaire. Result: ILR and DF were found properly placed at all the three (100%) CHCs. ILR and DF were connected to functional Voltage Sta- bilizer in two (66.66%) CHCs. A functional thermometer was placed inside every ILR and DF of all the three (100%) CHCs. Twice daily recording of temperature was found only in two CHCs (66.66%). The cabinet temperature of ILR and DFs was maintained in correct range in only two (66.66%) CHCs. Conclusion: The quality of immunization services can be improved by proper storage and management of vaccine in cold chain system. There is a need to improve methods of ILR and DF maintenance in terms of installation, temperature maintenance and regular defrost- ing with record keeping.